Implementasi Kebijakan Gerakan Literasi Sekolah Di Sekolah Dasar (Systematic Literature Review) - Marta, Rusdial; Murtadho, Nurul; Kusumaningrum , Shirly Rizki (Journal of Exploratory Dynamic Problems, 2024)
The research on the School Literacy Movement policy aims to describe a literature review on the implementation policy of the School Literacy Movement (GLS) in elementary schools. The researchers referred to articles using the keywords 'School Literacy Movement' or ‘Gerakan Literasi Sekolah’ in the Google Scholar, Scispace, and Scimagojr databases. This research was conducted in step-by-step stages, starting from article collection, article reduction, display, and discussion. This article is the result of an analysis based on literature regarding the subject being discussed. This study uses the Systematic Literature Review (SLR) methodology, with the PRISM protocol. The findings of the SLR study, analyzing 11 articles, indicate that the School Literacy Movement should be initiated from an early stage, starting from habituation, development, and implementation, and the role of parents should not be overlooked in the implementation of this GLS.